1995
DOI: 10.1017/s0021932000022860
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting choice of sterilisation among low income women in Paraíba, Brazil

Abstract: Despite the absence of a family planning programme, the prevalence of sterilisation in Brazil has increased substantially, such that it is used by relatively young women in poor areas of the country. Sterilisation is influenced more by the characteristics of the health service than by socioeconomic characteristics of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Also, with the positive correlation between antenatal care visits (particularly at least four visits) and births attended by skilled birth attendants in SSA [60][61][62], it is possible PLOS ONE that in countries where a high proportion of births are attended by skilled birth attendants, women may have received information about FPC as an effective contraceptive option to limit childbearing during antenatal care, thereby increasing their preference for it [63]. In Brazil, receiving antenatal care was found to be positively associated with the use of FPC [64]. The higher of odds of using FPC in countries with more doctors also illustrates the importance of access to the method, which is largely obtained through surgical procedures [65].…”
Section: Plos Onementioning
confidence: 99%
“…Also, with the positive correlation between antenatal care visits (particularly at least four visits) and births attended by skilled birth attendants in SSA [60][61][62], it is possible PLOS ONE that in countries where a high proportion of births are attended by skilled birth attendants, women may have received information about FPC as an effective contraceptive option to limit childbearing during antenatal care, thereby increasing their preference for it [63]. In Brazil, receiving antenatal care was found to be positively associated with the use of FPC [64]. The higher of odds of using FPC in countries with more doctors also illustrates the importance of access to the method, which is largely obtained through surgical procedures [65].…”
Section: Plos Onementioning
confidence: 99%
“…It has further been suggested that factors related to health systems, such as type or place of delivery, may exercise important influences on women's choice of sterilization. For example, the role of Caesarean delivery has been highlighted in conditioning the likelihood of postpartum tubal sterilization in some less developed BEMFAM, 1997;CESDEM et al 1997;INEI & Macro International, 1997. countries (Barros et al, 1986;Rutenberg & Ferraz, 1988;Chi & Thapa, 1993;Rodrigues & Moji, 1995). What remains unclear is the reasoning and causal direction of health system-related influences: whether women who have had multiple Caesareans are being sterilized for medical reasons, women are choosing Caesareans in order to facilitate getting a postpartum tubal ligation, or women who are better able to access health facilities are obtaining more medical services including Caesareans and sterilizations.…”
Section: Contextmentioning
confidence: 99%